Benefit Perception Analysis, Risk Perception, Hedonic Motivation, Psychological Factors, Web Design To Online Shop Purchase Decisions - Iin Emy Prastiwi; Tira Nur Fitria (Relevance: Journal of Management and Business, 2021)
This study aims to determine what factors influence consumer decisions to buy through an online shop. The factors that the researchers took were perceived benefits, perceived risks, hedonic motivation, psychological factors, and web design. This research is a quantitative study by taking a study at ITB AAS Indonesia. The population in this study were all academicians of ITB AAS Indonesia who have ever made purchases on the line shop. The sample in this study amounted to 142. The technique of collecting data by distributing questionnaires and interviews. The analytical method used is multiple linear regression analysis. The results obtained in this study are the variables of perceived usefulness, hedonic motivation, and web design have a positive and significant effect on online shop purchasing decisions. Meanwhile, risk perception and psychological factors do not have a significant effect.